Kecerdasan Emosional Berbasis Filsafat Humanisme dalam Praktik Pendidikan Modern: Emotional Intelligence Based on Humanist Philosophy in Modern Educational Practice - Ni Putu Sudayanti; I Nyoman Jampel; Desak Putu Parmiti; Dewa Bagus Sanjaya (Undiksha, 2026)
This article examines the integration of emotional intelligence with the principles of humanistic philosophy as a comprehensive approach in modern educational practice. The background of this study is rooted in the demands of 21st-century education, which emphasize not only cognitive abilities but also social-emotional competencies that shape learners’ character and humanity. The purpose of this study is to describe the nature of emotional intelligence, elaborate the principles of humanism in education, and analyze the conceptual relationship between the two as a foundation for developing more humanistic and learner-centered learning approaches. This study employs a literature review method, drawing on various up-to-date sources relevant to humanism, educational psychology, and emotional intelligence. The findings indicate that emotional intelligence plays a significant role in fostering self-regulation, empathy, and learners’ interpersonal skills, while humanistic philosophy provides ethical and pedagogical foundations that emphasize respect for human dignity, freedom, and potential. The integration of these two perspectives results in an educational model that positions learners as active, autonomous subjects who develop holistically. In instructional practice, this integration can be implemented through the strengthening of emotionally safe learning environments, self-reflective practices, positive interpersonal relationships, collaborative learning, and teachers’ emotional role modeling. In conclusion, humanism-based emotional intelligence is highly urgent in modern education, as it effectively addresses challenges related to character development, emotional maturity, and the quality of social relationships in learning. This article offers both a conceptual foundation and practical direction for educators in developing a more humanistic, inclusive, and contemporary learning ecosystem.